Relationship between Serum Uric Acid Levels and Nonalcoholic Fatty Liver Disease in Non-Obese Patients - Alihan Oral; Tolga Sahin; Fatih Turker; Erdem Kocak (Medicina, 2019)
Background and objectives: Nonalcoholic fatty liver disease (NAFLD) is associated with multiple factors such as hypertension, diabetes, dyslipidemia, obesity, and hyperuricemia. We aim to investigate the relationship between uric acid and NAFLD in a non-obese and young population. Materials and Methods: This study was performed in January 2010−2019 with a group of 367 (225 patients in the NAFLD group and 142 in the control group) patients with liver biopsy-proven NAFLD or no NAFLD. Patients with NAFLD were classified according to the percentage of steatosis as follows, group I had 1−20% and group II >20%. Demographic, clinical, and laboratory (biochemical parameters) features were collected retrospectively. Results: The mean body mass index (BMI) and age of the patients were 26.41 ± 3.42 and 32.27 ± 8.85, respectively. The BMI, homeostatic model of assessment (HOMA-IR), and uric acid (UA) values of the NAFLD group were found to be significantly higher than those of the controls. A positive correlation was found between the NAFLD stage and UA. The following factors were independently associated with NAFLD: BMI, HOMA-IR, and UA. In addition, the cut-off value of UA was 4.75 mg/dl with a sensitivity of 45.8% and a specificity of 80.3%. Conclusions: UA is a simple, non-invasive, cheap, and useful marker that may be used to predict steatosis in patients with NAFLD.